UNVEILING SOCIO-CULTURAL LAYERS IN PERUMAL MURUGAN’S ONE PART WOMAN (International Journal of Food and Nutritional Sciences, 2022)
The pain of childlessness felt by Kali and Ponna, the chief characters of the novel living in a rural farming community is hard enough as it is and the worse thing is that their happiness in based on fulfilling the dictates of the society. Even love and desire must meet the standards of the system and the social expectations and the stringent norms of caste and custom limit the opportunity and happiness of the couple. The paper examines the relationship of the couple with the society and how their enthralling tale of love takes a horrifying turn after Ponna’s visit to the annual chariot festival’s eighteenth night where consensual sex between unmarried men and women are accepted because all males are revered as gods. The paper dwells into the psyche of the couple and their sufferings and how the society is a threat to an individual’s happiness.